Dynamic properties of NH₃CH₂COOH·H₂PO₃ ferroelectric - Zachek, I.R.; Levitskii, R.R; Vdovych, A.S.; Bilenka, O.B. (Condensed Matter Physics, 2018)
Using a modified pseudospin model of NH₃CH₂COOH·H₂PO₃ ferroelectric taking into account the piezoelectric coupling with strains εi , ε₄, ε₅ and ε₆ within Glauber method in two-particle claster approximation, we have calculated components of dynamic dielectric permittivity tensor and relaxation times of the model. At the proper set of theory parameters, frequency and temperature dependences of the components of permittivity and temperature dependences of the relaxation times are studied. A satisfactory agreement of the theoretical results with experimental data for longitudinal permittivity is obtained.